2007
DOI: 10.1159/000101478
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Response to Inhaled Nitric Oxide Treatment for Intensive Care Unit Patients with Acute Respiratory Distress Syndrome

Abstract: Background: Inhaled nitric oxide (INO) can improve hypoxemia and reduce pulmonary hypertension, but there is a wide range of response to INO. Objectives: The aim of this study was to evaluate the effect of different INO concentrations in acute respiratory distress syndrome (ARDS) patients. Methods: Thirty-two adult ARDS patients who were supported by mechanical ventilator were included. INO was given at a concentration of 1, 5, 10, 20 and 40 ppm, sequentially. Arterial blood gas and mean pulmonary artery press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Respiratory failure with a high AaDO 2 level is a sign of tissue hypoxia. In such severely ill ARDS patients, tissue hypoxia is the primary cause of circulatory dysfunction, hypoxemia of the brain with unconsciousness, renal tubular necrosis in the kidneys, multiorgan failure and death [26, 27, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…Respiratory failure with a high AaDO 2 level is a sign of tissue hypoxia. In such severely ill ARDS patients, tissue hypoxia is the primary cause of circulatory dysfunction, hypoxemia of the brain with unconsciousness, renal tubular necrosis in the kidneys, multiorgan failure and death [26, 27, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…These patients frequently do not respond to standard ventilatory techniques and, thus, high levels of oxygen, high positive end-expiratory pressure (PEEP), and complementary and intermittent techniques such as prone positioning, recruitment maneuvers, and nitric oxide have been used in an attempt to maintain or increase oxygenation [1,2,3,4]. Presently, the comparison between the clinical effectiveness of conventional ventilation (CV) and other techniques is warranted almost solely by gas exchange analysis, mortality, and ventilator-free days; commonly, patients are defined as responders if their baseline Pa o 2 /Fi o 2 increases by 10–20% [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that iNO selectively relaxes vessels at the well-ventilated regions of the lung and that this results in improving the ventilation-perfusion mismatch and, therefore, improved oxygenation in ARDS patients [8]. In our case, iNO was considered to have redistributed pulmonary blood from the poorly ventilated regions to the well-ventilated regions.…”
Section: Discussionmentioning
confidence: 71%
“…The optimal dose of iNO to achieve the maximum effect in terms of improving oxygenation has been reported to vary from 1 to 20 ppm [8,[10][11][12], while high doses of iNO of [10 ppm [11,12] or [20 ppm [8] have also been shown to worsen oxygenation. One theory for this latter result is that a high dose of iNO can enter the poorly ventilated area, causing vasodilation of this area, possibly reducing the improvement in the ventilation-perfusion mismatch [8]. We started to administer iNO at 10 ppm to determine the patient's initial response to iNO and observed that iNO dramatically improved oxygenation without any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation